2022
DOI: 10.1186/s12885-022-09931-4
|View full text |Cite
|
Sign up to set email alerts
|

An integrative transcriptome analysis reveals potential predictive, prognostic biomarkers and therapeutic targets in colorectal cancer

Abstract: Background A deep understanding of potential molecular biomarkers and therapeutic targets related to the progression of colorectal cancer (CRC) from early stages to metastasis remain mostly undone. Moreover, the regulation and crosstalk among different cancer-driving molecules including messenger RNAs (mRNAs), long non-coding RNAs (lncRNAs) and micro-RNAs (miRNAs) in the transition from stage I to stage IV remain to be clarified, which is the aim of this study. Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 81 publications
0
19
0
Order By: Relevance
“…In recent years, finding molecular markers involved in the progression of cancer in humans has created a fascinating yet challenging field of research 31 , 32 . However, there are problems, such as the lack of more in-depth studies comparing precancerous stages to different stages of cancer with healthy subjects 33 .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, finding molecular markers involved in the progression of cancer in humans has created a fascinating yet challenging field of research 31 , 32 . However, there are problems, such as the lack of more in-depth studies comparing precancerous stages to different stages of cancer with healthy subjects 33 .…”
Section: Discussionmentioning
confidence: 99%
“…According to univariate Cox, LASSO, and multivariate Cox regression analysis, 8 m 5 CRlncRNAs (AC093157.1, LINC00513, AC025171.4, AC090948.2, ZEB1-AS1, AC109449.1, AC009041.3, and LINC02516) were determined to be significant prognostic factors to explore the prognostic function in CRC. In recent years, lncRNAs have been linked to cancer survival and development in many studies [ 27 , 28 ]. And ZEB1-AS1 was found to be a tumor-related lncRNA prognostic factor in CRC [ 29 ].…”
Section: Discussionmentioning
confidence: 99%
“… 54 miR-132 Up Tissue Samadi et al. 55 miR-193a, let-7g Up Serum Cho et al. 56 miR-21-5p Up Serum Fukada et al.…”
Section: Mirnas: Emerging Diagnostic Prognostic and Predictive Marker...mentioning
confidence: 99%
“… 54 Moreover, a transcriptome study identified miR-132 as a poor predictor of overall survival in CRC patients. 55 Exosomal miR-193a and let-7g high expression has been correlated with poor prognosis, recurrence, and venous and lymphatic invasion in CRC. 56 A prospective study investigated the changes of miR-21-5p in CRC patients before surgery and 1 and 6 months after surgery showing significantly higher miR-21-5p levels in relapsing plasma patients.…”
Section: Mirnas: Emerging Diagnostic Prognostic and Predictive Marker...mentioning
confidence: 99%